Prion disease risk uncertainties associated with urine-derived and recombinant fertility drugs. (19th July 2019) - Cashman, Neil R.; Tyshenko, Michael G.; Cheung, Ricky; Aspinall, Willy; Wong, Michelle; Krewski, Daniel
The detection of prion protein in widely used urine-derived fertility drugs has raised the possibility that prions from urine donors with (asymptomatic) prion disease could be present in these drugs. A high level of uncertainty exists regarding this issue. An international expert panel provided judgments related to prion disease transmission through fertility drug use in a structured expert elicitation. The elicitation gauged expert judgements about the uncertainty surrounding potential prion disease risks associated with urine-derived fertility drugs and emphasised the scientific ambiguity surrounding disease transmission risk factors associated with urine-derived fertility drugs. Group aggregated responses indicate that the theoretical risk of prion disease transmission with urine-derived fertility drugs was judged to be very low. The experts judged recombinant fertility drugs produced with bovine serum to possess 10-fold lower risk compared to urine-derived fertility drugs. Fertility drugs made without fetal bovine serum were judged to present a risk approximately 1, 200 times lower compared to urine-derived counterparts. This elicitation indicates recombinant fertility drugs carry relatively less risk than urine-derived fertility drugs. However, the associated uncertainties are significant and pro-active surveillance of possible new routes of transmission of human prion disease warrants consideration of new scientific data as it becomes available.